Innovative Complex Coacervates of Gelatin and Sodium Carboxymethyl Cellulose for Cinnamaldehyde Delivery: Impact of Processing Conditions on Characteristics and Bioactivity - Abdulla, Mahran; Xia, Shuqin (International Journal of Environment, Agriculture and Biotechnology, 2023)
Cinnamaldehyde (CA) has a special flavor, and numerous bioactivities; nevertheless, it possesses a high level of volatility, low solubility in water, and limited stability. To address the shortcomings of CA and enhance its use in foods, CA-loaded microcapsules were created by complex coacervation. Gelatin (GL) and carboxymethyl cellulose (CMC) were used as the wall materials of CA. Ideal conditions for obtaining encapsulation efficiency and morphology were found for core/wall ratio 1:1 (w: w), and an emulsification speed 15,000 rpm. The optimized microcapsule formulation demonstrates an encapsulation efficacy of 87.949 ± 1.229 % for CA with payload 41.276 ± 4.189% and a size of 26.093 ± 0.575μm. The examination of Fourier-transform infrared (FTIR) spectra of GL, CMC, GL-CMC complex coacervates and CA microcapsules exhibited an electrostatic attraction among GL and CMC molecules and the creation of hydrogen bonds among core (CA) and shell materials. When 1:1 core: wall ratio and 9000 rpm emulsification speed utilized in the microencapsulation of CA, the thermal stability significantly enhanced, possessed a slow-release property in ethanol 50%, and enhanced the antibacterial activity of CA.